2004
DOI: 10.1103/physreva.70.062715
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of initial-state effects in photo-double-ionization of Ne2s

Abstract: The triple-differential cross section (TDCS) for the photo-double-ionization of Ne and He leading to the Ne 2+ ͑2s −2 2p 6 ͒ and He 2+ ͑1s −2 ͒ states have been measured 20 eV above their respective thresholds in equal energy sharing conditions. The experimental results show that the Ne TDCS's are qualitatively different from the He ones. A calculation using the convergent close coupling method with a He-like final state and different initial-state wave functions clearly shows that the observed differences can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…The TDCSs of the He 2+ (1s −2 ) and Ne 2+ (2s −2 ) states have been measured at the same excess energy with respect to their relative threshold under unequal energy sharing conditions. As already found in an analogous study under equal energy sharing conditions [14], despite that the two cases share the same initial and final state symmetries some qualitative differences are observed in the TDCS. However, at variance with the equal energy sharing case the differences cannot be explained only as an initial state effect.…”
Section: Discussionsupporting
confidence: 76%
“…The TDCSs of the He 2+ (1s −2 ) and Ne 2+ (2s −2 ) states have been measured at the same excess energy with respect to their relative threshold under unequal energy sharing conditions. As already found in an analogous study under equal energy sharing conditions [14], despite that the two cases share the same initial and final state symmetries some qualitative differences are observed in the TDCS. However, at variance with the equal energy sharing case the differences cannot be explained only as an initial state effect.…”
Section: Discussionsupporting
confidence: 76%
“…It manifests itself in a non-Gaussian amplitude. A small non-Gaussian wing, with a minor contribution to the TDCS, was previously observed in DPI measurements on Ne 2s [32] and attributed to intershell (2s, 2p) mixing in the initial state. At variance in the present measurements an extended wing, which provides a dominant contribution to the TDCS, is observed.…”
mentioning
confidence: 81%
“…This is reflected in a large variety of patterns for the coincidence angular distributions. Moreover, it has been shown that the angular correlation patterns reveal effects due to the target initial state (Schaphorst et al 1995a, Bolognesi et al 2004b. Finally PDI may also proceed via an indirect process.…”
Section: Heavier Rare Gasesmentioning
confidence: 99%